2015
DOI: 10.1371/journal.pone.0128452
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Plasma Soluble Receptor for Advanced Glycation End-Products and Cardiovascular Outcomes in a Community-based Population: Results from the Atherosclerosis Risk in Communities Study

Abstract: Plasma soluble Receptor for Advanced Glycation End-products (sRAGE) is a strong marker of vascular outcomes although evidence on the direction of association is mixed. Compared to whites, blacks have lower levels of sRAGE. We hypothesized that genetic determinants of sRAGE would help clarify the causal role of sRAGE and the black-white difference in sRAGE levels. We conducted a genome-wide analysis of sRAGE in whites and blacks from the Atherosclerosis Risk in Communities Study. Median plasma sRAGE levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…However, higher GFR was independently associated with lower total sRAGE levels in Whites. Previous reports indicate that metabolic, lifestyle, and genetic factors explain close to 50% of the variability in total sRAGE [14, 28]. Our fully adjusted model accounted for 24% of the variability in total sRAGE and 14% of the variability in esRAGE.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, higher GFR was independently associated with lower total sRAGE levels in Whites. Previous reports indicate that metabolic, lifestyle, and genetic factors explain close to 50% of the variability in total sRAGE [14, 28]. Our fully adjusted model accounted for 24% of the variability in total sRAGE and 14% of the variability in esRAGE.…”
Section: Discussionmentioning
confidence: 75%
“…One study reported similar findings for esRAGE, albeit in a small number (n=25) of Afro-Caribbean patients with type 2 diabetes [10]. A recent genetics analysis showed that variants in the RAGE gene ( AGER ) do not account for racial differences in total sRAGE levels, suggesting that other biological or environmental factors are likely important [14]. Given that low sRAGE levels have been associated with type 2 diabetes, cardiovascular disease, and Alzheimer’s disease [15, 16] (i.e., diseases that disproportionately affect Black individuals), it is possible that the observed racial differences in sRAGE may contribute to racial disparities in chronic disease risk.…”
Section: Introductionmentioning
confidence: 81%
“…This receptor is expressed as membrane-bound (mRAGE) and soluble (sRAGE) forms; the latter is produced primarily by shedding of mRAGE (Raucci et al, 2008) and is thought to function as a ‘decoy’ receptor, preventing RAGE ligands from interacting with mRAGE, which would normally trigger inflammation (Schmidt, 2015). Of note, a non-synonymous variant (rs2070600) in the AGER gene (which encodes RAGE) is a strong determinant of serum sRAGE levels (Jang et al, 2007; Maruthur et al, 2015), with the rs2070600:C allele (encoding a Gly at position 82) being associated with increased sRAGE. This same allele is associated with decreased risk of allergic asthma (OR = 0.87, p=0.003 in [Ferreira et al, 2014]).…”
Section: Introductionmentioning
confidence: 99%
“…Other potential contributors to variation in previous studies include genetic and racial contributions to sRAGE, as sRAGE levels differ by race (14, 17) and 2 variants in the gene that encodes RAGE, AGER (advanced glycosylation end-product specific receptor), explain 26% of the variation in whites and 21.5% of the variation in blacks, but do not explain differences in sRAGE levels by race (24). Thus, inadequate control for race and genetic factors may have contributed to the variable findings in the literature.…”
mentioning
confidence: 99%